Colony field test reveals dramatically higher toxicity of a widely-used mito-toxic fungicide on honey bees (Apis mellifera). (15th January 2021) - Fisher, Adrian; DeGrandi-Hoffman, Gloria; Smith, Brian H.; Johnson, Meredith; Kaftanoglu, Osman; Cogley, Teddy; Fewell, Jennifer H.; Harrison, Jon F.
Abstract: Honey bees ( Apis mellifera ) and other pollinator populations are declining worldwide, and the reasons remain controversial. Based on laboratory testing, fungicides have traditionally been considered bee-safe. However, there have been no experimental tests of the effects of fungicides on colony health under field conditions, and limited correlational data suggests there may be negative impacts on bees at levels experienced in the field. We tested the effects of one of the most commonly used fungicides on colony health by feeding honey bee colonies pollen containing Pristine® (active ingredients: 25.2% boscalid, 12.8% pyraclostrobin) at four levels that bracketed concentrations we measured for pollen collected by bees in almond orchards. We also developed a method for calculating per-bee and per-larva dose. Pristine® consumption significantly and dose-dependently reduced worker lifespan and colony population size, with negative health effects observed even at the lowest doses. The lowest concentration we tested caused a 15% reduction in the worker population at an estimated dosage that was three orders of magnitude below the estimated LD15 values for previous acute laboratory studies. The enhanced toxicity under field conditions is at least partially due to activation of colonial nutritional responses missed by lab tests. Pristine® causes colonies to respond to perceived protein malnutrition by increasing colony pollen collection. Additionally, Pristine induces much earlier transitioning to foraging in individual workers, which could be the cause of shortened lifespans. These findings demonstrate that Pristine® can negatively impact honey bee individual and colony health at concentrations relevant to what they experience from pollination behavior under current agricultural conditions. Graphical abstract: Image 1 Highlights: Fungicides are not considered highly toxic to honey bees. A mito-toxic fungicide reduced worker lifespan and colony population. Fungicide exposure induced early foraging. Lethal effects occurred at concentrations lower than lab measurements. The safety of fungicides for pollinators must be re-evaluated using colony-level assays. Abstract : Capsule: Honey bee colonies exposed to concentrations of a mito-toxic fungicide in pollen at concentrations similar to what they receive while foraging in a sprayed orchard experienced a dose-dependent reduction in worker lifespan, reducing colony populations. Lethal effects were observed at concentrations three orders of magnitude lower than in lab studies demonstrating the need for re-evaluation of fungicide safety.